2005
DOI: 10.1021/ja0556934
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular C−H Bond Activation Promoted by a Titanium Alkylidyne

Abstract: The transient titanium alkylidyne complex (PNP)TiCtBu (PNP = N-[2-P(CHMe2)2-4-methylphenyl]2-), prepared from alpha-hydrogen abstraction of the corresponding alkylidene-alkyl species (PNP)Ti=CHtBu(CH2tBu), can readily undergo intermolecular 1,2-addition of C-H bonds of benzene and SiMe4. Synthesis and reactivity, isotopic labeling, kinetics, and theoretical studies strongly favor an alkylidyne pathway and the alpha-H abstraction step to be the rate-determining step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
137
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 18 publications
(16 reference statements)
12
137
0
Order By: Relevance
“…[75] A similar version of this reaction has also been observed between a titanium phosphinidene and N 2 CPh 2 . [78] The ability to generate transient titanium alkylidynes [119,120] [103] Another documented case of a Wittig-like reaction to produce titanium imides was reported by Richeson and coworkers. [54] In their studies a bis-guanidinate titanium bisalkyl underwent double insertion of a bulky isonitrile NCAr (Ar = 2,6-Me 2 C 6 H 3 ) to eventually afford the terminal aryl imide [{(Me 2 N)CA C H T U N G T R E N N U N G (NiPr 2 ) 2 } 2 Ti=NAr] (Scheme 25).…”
Section: Wittig-like Reactionsmentioning
confidence: 98%
“…[75] A similar version of this reaction has also been observed between a titanium phosphinidene and N 2 CPh 2 . [78] The ability to generate transient titanium alkylidynes [119,120] [103] Another documented case of a Wittig-like reaction to produce titanium imides was reported by Richeson and coworkers. [54] In their studies a bis-guanidinate titanium bisalkyl underwent double insertion of a bulky isonitrile NCAr (Ar = 2,6-Me 2 C 6 H 3 ) to eventually afford the terminal aryl imide [{(Me 2 N)CA C H T U N G T R E N N U N G (NiPr 2 ) 2 } 2 Ti=NAr] (Scheme 25).…”
Section: Wittig-like Reactionsmentioning
confidence: 98%
“…Serving as a promising alternative of activating both sp 2 and sp 3 CH bonds under mild conditions, the mechanism of methane 1,2‐addition reaction via titanium alkylidyne intermediate, (PNP)TiC t Bu (PNP = N [2‐P i Pr 2 ‐4‐methylphenyl] 2 ‐ ), generated through α‐hydrogen abstraction from the titanium alkylidene (PNP)Ti = CH t Bu( CH2normaltBu), has been investigated in both experiment and theory by Mindiola's group and Ninković et al As shown in Figure , the complex 1 features not only the less expensive titanium rather than those metals commonly utilized in CH activation, but also reverse hydrogen abstraction rather than photochemical activation in generating the transient titanium alkylidyne complex A, the involvement of which was validated in the CH activation of benzene and methane by Mindiola and coworkers experimentally, where the formation of complex A was demonstrated to be the rate‐determining step via mechanistic investigation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of terminal trimethylsilylmethylidene metal complexes plummets dramatically when the metal in question represents the lighter congener for each group (e.g., Ti, V, Cr) [2,[15][16][17][18]. In contrast, group 4 transition metal compounds bearing the terminal trimethylsilylmethylidene ligand are even more scant, with the only reported examples (isolable) being the titanium and zirconium complexes (PNP)Ti@CHSiMe 3 (X) (PNP À = N[2-P(CHMe 2 ) 2 -4-methylphenyl] 2 ) [19][20][21][22]; X À = OTf [23], CH 2 SiMe 3 [17]) and [C 5 H 3 (SiMe 2 P i Pr 2 ) 2 ]Zr@CHSiMe 3 (Cl) [24,25], respectively. In most cases, the M = CHSiMe 3 functionality in question must be trapped or generated in situ, to avoid decomposition pathways from occurring [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The only examples of a titanium complexes bearing the terminal trimethylsilylmethylidene unit were recently reported by us, and involved the compounds (PNP)Ti@ CHSiMe 3 (X) (X À = OTf [23], CH 2 SiMe 3 [17]). Rothwell and co-workers have reported bridging trimethylsilylmethylidene complexes of titanium [30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation